Integrating Decomposers, Methane-Cycling Microbes and Ecosystem Carbon Fluxes Along a Peatland Successional Gradient in a Land Uplift Region - Juottonen, Heli; Kieman, Mirkka; Fritze, Hannu; Hamberg, Leena; Laine, Anna M.; Merilä, Päivi; Peltoniemi, Krista; Putkinen, Anuliina; Tuittila, Eeva-Stiina (Springer, 2022)
Peatlands are carbon dioxide (CO2) sinks that, in parallel, release methane (CH4). The peatland carbon (C) balance depends on the interplay of decomposer and CH4-cycling microbes, vegetation, and environmental conditions. These interactions are susceptible to the changes that occur along a successional gradient from vascular plant-dominated systems to Sphagnum moss-dominated systems. Changes similar to this succession are predicted to occur from climate change. Here, we investigated how microbial and plant communities are interlinked with each other and with ecosystem C cycling along a successional gradient on a boreal land uplift coast. The gradient ranged from shoreline to meadows and fens, and further to bogs. Potential microbial activity (aerobic CO2 production; CH4 production and oxidation) and biomass were greatest in the early successional meadows, although their communities of aerobic decomposers (fungi, actinobacteria), methanogens, and methanotrophs did not differ from the older fens. Instead, the functional microbial communities shifted at the fen–bog transition concurrent with a sudden decrease in C fluxes. The successional patterns of decomposer versus CH4-cycling communities diverged at the bog stage, indicating strong but distinct microbial responses to Sphagnum dominance and acidity. We highlight young meadows as dynamic sites with the greatest microbial potential for C release. These hot spots of C turnover with dense sedge cover may represent a sensitive bottleneck in succession, which is necessary for eventual long-term peat accumulation. The distinctive microbes in bogs could serve as indicators of the C sink function in restoration measures that aim to stabilize the C in the peat.
Keywords: ecosystem respiration; methane emission; fungi; actinobacteria; methanogens; methanotrophs; microbial biomass; microbial community; primary paludification; peatland development; ecosystem respiration; methane emission; fungi; actinobacteria; methanogens; methanotrophs; microbial biomass; microbial community; primary paludification; peatland development